The Effect of Whole-Body Vibration on Upper Extremity Function in Children with Cerebral Palsy: A Pilot Study - Marianna Kelaiditi; Alexandra Lepoura; Anna Christakou; Nikolaos Chrysagis; Vasiliki Sakellari (Applied Sciences)
Cerebral palsy (CP) is the leading cause of lifelong physical disability, affecting approximately 17 million individuals worldwide. Upper extremity dysfunction, alongside spasticity and coordination challenges, significantly impacts independence in daily activities. Whole-Body Vibration (WBV) has been proposed as a therapeutic modality to improve functionality in neurological populations, though its effects on upper extremity function in children with CP remain relatively unclear. This pilot study assessed the feasibility and preliminary efficacy of Upper Extremity Vibration Therapy using a Whole-Body Vibration Platform (UEVT-WBV) combined with conventional physiotherapy, in enhancing upper extremity function and reducing spasticity in children with CP. Ten children aged 4.5–18 years with upper extremity dysfunction due to CP were randomly assigned to either an intervention group receiving UEVT-WBV alongside conventional physiotherapy or a control group receiving only conventional physiotherapy. Both interventions were implemented over eight weeks. Assessments were conducted at baseline, week 4, and week 8 using the Modified Ashworth Scale (MAS) (spasticity), ABILHAND (manual ability), and a quality-of-life questionnaire. Both groups demonstrated significant reductions in spasticity and improvements in upper extremity function over time, as measured by MAS and ABILHAND, respectively. However, no statistically significant differences were found between groups, indicating comparable outcomes between UEVT-WBV and conventional physiotherapy alone. While hemiplegic participants achieved greater functional gains than those with quadriplegia regardless of intervention, quality-of-life improvements were minor and limited to emotional well-being and pain reduction in the intervention group. This pilot study highlights the feasibility of UEVT-WBV as an adjunct therapy in pediatric CP rehabilitation, providing foundational data for future studies. Further studies are needed to isolate the effects of UEVT-WBV and to identify its potential in targeted subpopulations.